Availability of data on nutrition intervention coverage in West Africa: Technical note - Transform Nutrition West Africa (International Food Policy Research Institute, 2021)
Transform Nutrition West Africa is a regional initiative to support effective and programmatic action on nutrition through evidence generation, synthesis, and mobilization. Intervention coverage data is essential for tracking the implementation and impact of strategies and investments to reduce malnutrition. This technical provides the methodological details of the assessment of a country’s potential to report on national-level coverage for a set of 16 key nutrition interventions in West Africa. Interventions were prioritized by regional stakeholders. We reviewed the availability of coverage data for 16 nutrition interventions grouped along the maternal, newborn, child, adolescent continuum of care. Data were reviewed and key actions recommended to strengthen coverage measurement. Results are presented in individual country data profiles, and a detailed database is available for download.